Perception and practices of homemakers regarding extra salt consumption in tripura: A rural versus urban comparison - Anjan Datta; Nabarun Karmakar; Kaushik Nag; Partha Bhattacharjee (Wolters Kluwer Medknow Publications, 2022)
Introduction: India has diverse dietary culture where salt and spices are used extensively, but up-to-date figures on population salt consumption are very limited. Objectives: The objective of this study is to assess the perception and practices of females doing household cooking regarding extra salt consumption and to have a rural-urban comparison on a specified population. Materials and Methods: A community-based cross-sectional study was conducted among 480 homemakers residing in a rural and urban (Madhupur, Sepahijala district and Dukli, West Tripura district, respectively) area of Tripura for a period of 6 months. A predesigned, pretested, semi-structured interview schedule divided into two parts was used to collect the required information, and scores were given for each response regarding perception and practice of the participants. Results: The mean age of the respondents was 38.48 ± 14.063 years and 37.30 ± 12.087 years, respectively, for rural and urban areas, and both the populations were comparable in their baseline characteristics. Majority of the participants believed recommended daily salt consumption per person daily was >5-10 g (62.9% of rural and 59.6% of the urban participants) which was too high, and significant difference (P value 0.002) was found in practice regarding extra salt consumption among rural and urban participants. Conclusion: This study revealed good perception and significantly better practice regarding extra salt consumption among the urban population. Social caste in the rural population and socioeconomic status in both the study groups were the factors responsible for extra salt consumption in this study.